Rancang Bangun Sistem Informasi Pendataan Penduduk Dikantor Kelurahan Kotaratu Kabupaten Ende - Siti Soraya; Ferdinandus Lidang Witi (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2021)
Currently, not many urban vilages in Indonesia, especially in Ende Regency, make nlne population data reports. With the existing benefits and conveniences, this system should be developed by each keurahan.in this case, it is in line with advances in information and communication technology such as internet and web tecnologies that support the process input and output data quickly and accurately, especially in collecting data on residents in the Kota ratu village. In the current pandemic (Covid-19), information technology is very much needed, because the government implements large-scale sosial rules or restrictions in the context of handling Covid-19. In this social restriction effort, the Indonesian government has also limited activities outside the home. As we know, population data collection is generaly done manually, i.e. village Officers come to residents’ homes to collect data so that the time required becomes inefficient. This study aims to design a population dat collection information system at the Kota Ratu District Office, Ende Regency, so that it can make it easier for village employees to carry out population data collection processes and monthly reports. The software development method used is the waterfall method. Data collection techniques in this study used interviews, obsevation and literature study. This research can also produce a population data collection information system that can present information quicky and efficiently and can present the necessary reports.